The Mediating Role of Commitment Organizational Dimensions Between Job Involvement on Employee Performance: A Cross-Sectional Study - Suparna, Dade; Noor, Juliansyah (APMBA (Asia Pacific Management and Business Application), 2021)
Organizations often cite high job involvement as a critical success factor in achieving higher performance, and it is reinforced by three dimensions of engagement. Therefore, this study was performed to evaluate the functions of three dimensions of organizational commitment regarding employee performance and job involvement. This research was performed via a survey of 346 National Private Banks' supervisors and employees in Banten Province, Indonesia. Then, the hypothetical relationship of the collected data was tested by applying the partial least-squares structural equation. Consequently, the results showed that job involvement influenced normative and affective commitment. These two dimensions were also noted to significantly affect employee performance. Finally, the association between employee performance and job involvement was shown to be influenced by affective commitment. On the contrary, normative and continuance commitment did not mediate this relationship. There was also no support for continuance and normative commitments nor the relationship of job involvement with employee performance. Therefore, job involvement improves employee performance through affective commitment. This implies that human resources managers need to through available resources to promote job involvement and the three dimensions of organizational commitment in their employees. Further study is recommended to test the mediating effect on this relationship